Bending the rules: a novel approach to placement and retrospective experience with the 5 French Arndt endobronchial blocker in children <2 years. Issue 5 (9th March 2016) - Templeton, T. Wesley; Downard, Martina G.; Simpson, Christopher R.; Zeller, Kristen A.; Templeton, Leah B.; Bryan, Yvon F.
Summary: Background: One‐lung ventilation (OLV) is frequently employed to improve surgical exposure during video‐assisted thoracoscopic surgery (VATS) and thoracotomy in adults and children. Because of their small size, children under the age of 2 years are not candidates for some of the methods typically used for OLV in adults and older children, such as a double‐lumen endotracheal (DLT) tube or intraluminal use of a bronchial blocker. Due to this, the clinician is left with few options. One of the most robust approaches to OLV in infants and small children has been the extraluminal placement of a 5 French (5F) Arndt endobronchial blocker (AEB). Aim: The aim of this retrospective study was to examine and describe our experience with placement and management of an extraluminal 5F AEB for thoracic surgery in children <2 years of age. Methods: We retrospectively examined the anesthetic records for details of AEB placement, arterial blood gas (ABG) data, and intraoperative analgesic prescription in 15 children under the age of 2 years undergoing OLV with a 5F AEB for thoracic surgery at our institution from January 2010 through January 2016. Results: We were able to successfully achieve lung isolation in 14 of 15 patients using a 5F AEB that was bent 35–45° 1.5 cm proximal to the inflatable cuff. In 13 of 15 patients, we were able to place the AEB into final position with the aid of video‐assisted fiberoptic bronchoscopy. In two patients, fluoroscopy was required to place the 5F AEB into the left mainstem due to poor visualization of the carina and rapid desaturation during bronchoscopy. In one of these patients, even though the blocker appeared to be correctly placed by fluoroscopy, adequate lung isolation was not observed. Intraoperatively, we observed significant degrees of hypercarbia in most patients without oxygen desaturation. Analgesic regimens lacked consistency and varied among patients. Open thoracotomy procedures tended to receive more aggressive narcotic regimens than video‐assisted thoracoscopic surgery (VATS) procedures. Fourteen of 15 patients were extubated in the immediate postoperative period. Conclusions: Our technique of placing a 35–45° bend in the AEB, extraluminal placement, and observed manipulation with a video‐assisted flexible fiberoptic bronchoscope (FFB) within the trachea can be used to achieve consistent lung isolation in patients <2 undergoing thoracic surgery. When the use of a FFB proves unsuccessful, fluoroscopy can provide an alternative solution to successful placement. Significant respiratory derangements without long‐term sequelae will occur in a majority of these patients during OLV. Several different approaches to intraoperative analgesia did not impede extubation in the early postoperative period. Abstract :